Insomnia in the elderly – characteristics of plausible reasons - Jankowska, Paula; Jankowski, Krzysztof; Rudnicka-Drożak, Ewa (Journal of Education, Health and Sport, 2018)
IntroductionInsomnia is one of the most common sleep disorders affecting a very large percentage of the general population. This can be visualized by reporting insomnia by up to 50% of patients attending a family doctor. In the elderly population the prevalence of sleep disorders most often in the form of insomnia is even higher. Physical and mental health problems and behavioral determinants may affect insomnia. Moreover, sleep pattern in healthy older individuals substantially changes with age. ObjectiveThe aim of this study is to present various factors influencing insomnia in the elderly and depict clinical picture of this medical problem. ResultsArticle depicted common medical reasons of insomnia.ConclusionsSleep problems in elderly have a very diverse background. Aging of individuals results in changed sleep architecture and total sleep duration. According to this facts, some older patients may have not realistic expectations regarding sleep length, not real sleep problems. Physical illnesses are plausible reasons of even severe insomnia, including chronic musculoskeletal pain, cardiovascular diseases like heart failure or ishaemic heart disease, rhinitis and nasal congestion, chronic obstructive pulmonary disease or gastroesophageal reflux disease. Nocturia is also reported as frequent reason of awakenings in elderly. Menopausal hot flashes also make sleep intermittent. One of the common reasons of insomnia as well as daily symptoms is obstructive sleep apnea, often undiagnosed, as it remains interpreted as only snoring. Mental health problems as depression, anxiety and dementia have a considerable impact on sleep quality.